Intermolecular interactions in crystalline 1-(adamantane-1-carbonyl)-3-substituted thioureas with Hirshfeld surface analysis - Saeed, Aamer (2015)
The conformationally congested species 1-(adamantane-1-carbonyl)-3-(2,4,6-trimethylphenyl)thiourea has been prepared and fully characterized by elemental analyses, FTIR, 1H NMR, 13C NMR and mass spectrometry. Its crystal structure was determined by single-crystal X-ray diffraction. The dihedral angle between the plane of the 2,4,6-trimethylphenyl group and the plane of the thiourea fragment was optimized by theoretical calculations applying the B3LYP/6-311++G(d,p) level for the purpose of investigating the conformational effects on the stabilization of the crystal packing. A detailed analysis of the intermolecular interactions in a series of six closely related phenylthiourea species bearing the 1-(adamantane-1-carbonyl) group has been performed based on the Hirshfeld surfaces and their associated two-dimensional fingerprint plots. The relative contributions of the main intermolecular contacts as well as the enrichment ratios derived from the Hirshfeld surface analysis establish the 1-acyl thiourea synthon to be a widespread contributor.